Intracardiac thrombosis after congenital heart disease surgeries in neonates: a report of two cases - Yanlin Yang; Jing Lv; Yajiao Li; Changping Gan; Peng Ji (BMC, 2023)
Abstract Background Intracardiac thrombosis (ICT) is a rare complication after the cardiopulmonary surgery for interrupted aortic arch (IAA) or total anomalous pulmonary venous connection (TAPVC) without previous records. There are still no general guidelines regarding as the mechanism or management of postoperative ICT in neonates and younger infants. Case presentation We reported the conservative and surgical therapies in two neonates with intra-ventricular and intra-atrial thrombosis after the anatomical repair for IAA and TAPVC, respectively. There were no risk factors for ICT in both patients, except for the use of blood product and prothrombin complex concentrate. The surgery was indicated after TAPVC correction due to the worsening respiratory status and rapidly decreased mixed venous saturation. Anticoagulation combined with antiplatelet therapies was adopted in another patient. These two were both finally recovered, and three-month, six-month, and one-year follow-up echocardiography revealed no abnormality. Conclusions ICT is uncommon in pediatric population after the surgery for congenital heart disease. Single ventricle palliation, heart transplantation, longer central line use, post-extracorporeal membrane oxygenation, and massive blood product use are major risk factors for postcardiotomy thrombosis. The causes of postoperative ICT are multifactorial, and the immaturity of thrombolytic and fibrinolytic system in neonates may serve as a prothrombotic factor. However, no consensus reached regarding as the therapies for postoperative ICT, and the large-scale prospective cohort study or randomized clinical trial is needed.